Epithelioid trophoblastic tumor: a case report. Issue 3 (1st April 2006) - Lo, C.; Low, I.; Tan, A. L.; Baranyai, J.
Abstract : Epithelioid trophoblastic tumor is a rare and distinctive pathologic entity within the complex family of gestational trophoblastic disease. We describe a case of epithelioid trophoblastic tumor occurring in a 34-year-old woman, who presented with a large uterine tumor 3 years following an uncomplicated pregnancy. The clinicopathologic findings in this case are typical of this unusual entity and consistent with current literature, with the exception of negative beta-human chorionic gonadotrophin levels. The distinguishing features from other intermediate trophoblastic tumors and tumor-like lesions are discussed.